Information Transparency of the Activity of the Enterprise as Taxpayers: Financial Reporting Capabilities and Ways if Increasing of its Quality - Kuzmenko, H.; Shalimova, N.; Кузьменко, Г. І.; Шалімова, Н. С. (PS Global, 2018)
The article discloses the ways of ensuring information transparency regarding the tax relations of the enterprise in the system of financial reporting. It is substantiated that the necessity of disclosing information about tax relations of an enterprise is the result of such qualitative characteristics of financial reporting as appropriateness and two principles of its preparation: the principle of full coverage and the principle of continuous activity. The information about tax relations of a company which should be classified in the categories of events after the balance sheet date, taking into account the requirements of tax legislation is disclosed. The format for disclosing information on the qualitative state of taxation at the enterprise in the notes to the financial statements is proposed taking into account the requirements of the Tax Code of Ukraine concerning the procedure of administering taxes, fees and obligatory payments.
Keywords: financial reporting; notes to the annual financial reporting; events after the balance sheet date; tax relations; calculations with the budget